Fieldwork under fire : contemporary studies of violence and survival - Nordstrom, Carolyn, 1953-; Robben, Antonius C. G. M. (Berkeley : University of California Press, 1995)
This title presents a collection of essays written by anthropologists who have experienced the unpredictability and trauma of political violence firsthand. These essays combine theoretical, ethnographic, and methodological points of view to illuminate the processes and solutions that characterize life in dangerous places.
Croatian war experience / Maria B. Olujic -- Anthropologist as terrorist / Joseba Zulaika -- Ethnographic states of emergency / Allen Feldman -- Myrna Mack / Elizabeth Oglesby -- Reflections on an "Antropología Comprometida" : conversations with Ricardo Falla / Beatriz Manz -- Reflections on managing danger in fieldwork : dangerous anthropology in Belfast / Jeffrey A. Sluka.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Ethnology -- Fieldwork; Violence -- Research; Violence -- Moral and ethical aspects; Ethnologists -- Crimes against; Anthropological ethics; Ethnologie -- Recherche sur le terrain; Violence -- Recherche; Violence -- Aspect moral; Ethnologues, Crimes contre les; Anthropologues -- Déontologie.; Ethnologues -- Crimes contre; SOCIAL SCIENCE -- Violence in Society; Anthropological ethics; Ethnology -- Fieldwork; Violence -- Moral and ethical aspects; Violence -- Research; Gewalt; Feldforschung; Anthropologie; Ethnologe; Ethnologie; Veldwerk; Antropologen; Geweld; Anthropology; Social Sciences; Social & Cultural Anthropology; Violence -- Recherche; Violence -- Aspect moral; Ethnologie -- Recherche sur le terrain; Ethnologues -- Crimes contre